Reverse engineering gene regulatory circuitries in neural crest development and evolution - Candido-Ferreira, IL (2021)
The neural crest (NC) is an emblematic population of embryonic, stem-like cells characterised by their unique multipotency, migratory behaviour and broad developmental potential. Acquisition of these cells represents one major evolutionary transition in the tree of life, endowing vertebrates with their unique body plan.